Essays in asset pricing - Lee, RCY (2023)
This thesis consists of three essays investigating the asset pricing implications of technologies and corporate adaptation. The first essay examines the role and impact of technology stocks on the value premium. The second essay shows the value and risk implications of corporate adaptation to the Covid crisis based on information shocks from voluntary work-from-home announcements. The third essay studies firms’ stock and operational performances in adopting new technologies.